2018
DOI: 10.1051/epjconf/201817702005
|View full text |Cite
|
Sign up to set email alerts
|

Topology-based description of the NCA cathode configurational space and an approach of its effective reduction

Abstract: Abstract. Modification of existing solid electrolyte and cathode materials is a topic of interest for theoreticians and experimentalists. In particular, it requires elucidation of the influence of dopants on the characteristics of the studying materials. For the reason of high complexity of the configurational space of doped/deintercalated systems, application of the computer modeling approaches is hindered, despite significant advances of computational facilities in last decades. In this study, we propose a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, the proposed set of structure-based descriptors was proved to be successful in reducing the complexity of the CCS. 19 Those previous modeling insights and additional experimental results 6 motivated the current work. We now propose an extension of the combined CCS-DFT-ML approach to illuminate structural and compositional influences on the reported experimental nonmonotonic behavior of diffusion activation energy for the doped K 1−x Fe 1−x Ti x O 2 solid electrolyte with increasing doping concentration.…”
Section: ■ Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, the proposed set of structure-based descriptors was proved to be successful in reducing the complexity of the CCS. 19 Those previous modeling insights and additional experimental results 6 motivated the current work. We now propose an extension of the combined CCS-DFT-ML approach to illuminate structural and compositional influences on the reported experimental nonmonotonic behavior of diffusion activation energy for the doped K 1−x Fe 1−x Ti x O 2 solid electrolyte with increasing doping concentration.…”
Section: ■ Introductionmentioning
confidence: 85%
“…We showed that the prediction of crystal structure formation energies resulted in a high accuracy (mean absolute error <2 meV/ion). Moreover, the proposed set of structure-based descriptors was proved to be successful in reducing the complexity of the CCS . Those previous modeling insights and additional experimental results motivated the current work.…”
Section: Introductionmentioning
confidence: 99%
“…4 in the deintercalation range of 0 < x ≤0.5. Thus, the reduced CCS is comparable in complexity with that obtained within the recently proposed machine learning, DFT calculations, and geometrical-topological analysis combined approach [11] remaining applicable in the whole range of delithiation.…”
Section: Conclusion and Remarksmentioning
confidence: 69%
“…On the other hand, the results obtained in this work clearly demonstrate advantages of CS consideration in combination with geometrical-topological and DFT approaches. Furthermore, selection of a proper set of geometrical-topological descriptors leading to strong correlations between structure and energy properties of ion transport allows one to reduce CS size for complex systems within the machine learning algorithms [12]. Thus, for the case of disordered structures, the proposed approach can be considered as an extension of the topology-based search algorithms for prospective solid electrolytes [13][14][15].…”
Section: Conclusion and Remarksmentioning
confidence: 99%